Influence of double excitation AC/DC in the reactive power demand of 3-phase transformers - Rossi, Jose Carlos [UNESP]; Oliveira, Luis Carlos Origa de [UNESP]; Ferreira, Marco A S [UNESP] (IEEE, 1999)
In this work it is discussed the performance of the reactive power demand in three-leg transformer core and three-phase transformer bank, under different conditions of AC/DC double excitation. In order to analyse the influence of double excitation in reactive power theoretically a mathematical model was developed considering the mutual coupling between phases and the magnetic nonlinearity. The validity of the proposed model is verified by means of the experimental and simulated results.
Keywords: Approximation theory; Computer simulation; Electric currents; Electric excitation; Electric resistance; Magnetic circuits; Magnetization; Mathematical models; Reactive power; Leakage inductance; Magnetic nonlinearity; Three phase transformer; Transformer bank; Electric transformers